2020
DOI: 10.1016/j.matt.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capillary-Driven Additive Manufacturing of Continuous Carbon Fiber Composite

Abstract: This composite 3D-printing technology is based on a capillary effect through thermal gradient applied onto carbon fibers to allow deposited liquid polymers to simultaneously flow and become solid so as to form 3D structures. We also developed a robotic system consisting of a uniquely designed printing head and an automated robot arm, yielding a 3D printer that enables us to print a thermosetting composite with arbitrary shape and complex geometry on 2D and 3D substrates or in free space without supporting stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 37 publications
(39 reference statements)
0
36
0
Order By: Relevance
“…On the other hand, the use of low volume fraction (i.e., 10 wt%) enables a complex component additive manufacturing (Figure 3 (C)), establishing the challenge of optimizing the AM process for high fiber content, suitable for structural applications. [36] Based on Shi et al, [12] Sanei et al [27] , and Van de Werken et al, [7,39] Figure 4 exhibits the mechanical property variation associated with the fiber size and the working temperature based on the glass transition temperature (T g ) of the matrix. As previously mentioned, the increase in fiber size increases the mechanical behavior; meanwhile, the working temperature is governed mainly by the matrix (thermoplastic or thermoset).…”
Section: Additive Manufacturing Of Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the use of low volume fraction (i.e., 10 wt%) enables a complex component additive manufacturing (Figure 3 (C)), establishing the challenge of optimizing the AM process for high fiber content, suitable for structural applications. [36] Based on Shi et al, [12] Sanei et al [27] , and Van de Werken et al, [7,39] Figure 4 exhibits the mechanical property variation associated with the fiber size and the working temperature based on the glass transition temperature (T g ) of the matrix. As previously mentioned, the increase in fiber size increases the mechanical behavior; meanwhile, the working temperature is governed mainly by the matrix (thermoplastic or thermoset).…”
Section: Additive Manufacturing Of Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…The thermoset matrices allow the material application at higher glass transition due to the strong molecular cross-link interaction compared with thermoplastic matrices used for AM. [12] The fiber size used also limits the AM method to be employed, in which the fused filament fabrication (FFF) and localized in-plane thermal assisted (LITA) present methods of impregnating long fibrous reinforcement. [12,32] On the other hand, direct ink writing (DIW) and stereolithography (SLA) processing are useful for short fibers.…”
Section: Additive Manufacturing Of Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…It also reduces warping and enables a larger build envelope [121]. Shi et al [122] reported a dynamic capillary-driven additive manufacturing approach for manufacturing of continuous carbon fiber composites. This approach offers control over viscosity and degree of curing of carbon fiber composites.…”
Section: Fiber Reinforced Polymer Compositesmentioning
confidence: 99%